2021
DOI: 10.3389/fpubh.2021.663045
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection or Reactivation of Severe Acute Respiratory Syndrome Coronavirus 2: A Systematic Review

Abstract: As the pandemic continues, individuals with re-detectable positive (RP) SARS-CoV-2 viral RNA among recovered COVID-19 patients have raised public health concerns. It is imperative to investigate whether the cases with re-detectable positive (RP) SARS-CoV-2 might cause severe infection to the vulnerable population. In this work, we conducted a systematic review of recent literature to investigate reactivation and reinfection among the discharged COVID-19 patients that are found positive again. Our study, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 86 publications
2
27
1
Order By: Relevance
“…Not all re-positive cases >3 months after first infection should be assumed to correspond to reinfection. In our study, of the 4 recurrences identified that involved the same strain, 2 also occurred within this period, whereas the remaining 2 occurred 55 and 77 days after the first episode, beyond the threshold proposed as highly suggestive of nonreinfections ( 25 , 30 ).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Not all re-positive cases >3 months after first infection should be assumed to correspond to reinfection. In our study, of the 4 recurrences identified that involved the same strain, 2 also occurred within this period, whereas the remaining 2 occurred 55 and 77 days after the first episode, beyond the threshold proposed as highly suggestive of nonreinfections ( 25 , 30 ).…”
Section: Discussionmentioning
confidence: 45%
“…Other studies have tried to go beyond the reporting of single cases by offering data on the frequency of SARS-CoV-2 reinfections in different countries; results range from 0.14 to 2.11% ( 19 – 24 ). However, in all these studies, the assignment of reinfections was supported only by sequential positive RT-PCR results, which means that, strictly speaking, these re-positive SARS-CoV-2 infections were considered suspected reinfections ( 22 ) without determining whether they were recurrences involving the same strain, reinfections, persistent cases, or testing errors ( 25 ). Assigning re-positive cases to 1 of the above categories is only possible when whole sequencing data are also included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that most of the top 12 African countries with the most COVID-19 deaths reported their first COVID-19 case(s) between February and March 2020 (see Supplementary Table S1), which indicates that most of the stringency index policies are similar in most countries in Africa. Future work plans to extend the current study by incorporating possible reinfection or vertical transmission in the model to explore its impact on the overall transmission dynamics in African countries (Tang et al 2021 ; Musa et al 2021c ).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of reinfections has been persistently low throughout the literature. A systemic review on reinfection involving 113,715 patients highlighted that most reports quote a low reinfection rate of 1% amongst populations 20 . These ndings suggest that the risk of reinfection to the public health is low.…”
Section: Discussionmentioning
confidence: 99%